Validity of rapid estimates of household wealth and income for health surveys in rural Africa - Morris, Saul Sutkover; Carletto, Calogero; Hoddinott, John F.; Christiaensen, Luc (BMJ, 2000)
STUDY OBJECTIVE -- To test the validity of proxy measures of household wealth and income that can be readily implemented in health surveys in rural Africa. DESIGN -- Data are drawn from four different integrated household surveys. The assumptions underlying the choice of wealth proxy are described, and correlations with the true value are assessed in two different settings. The expenditure proxy is developed and then tested for replicability in two independent datasets representing the same population. SETTING -- Rural areas of Mali, Malawi, and Côte d'Ivoire (two national surveys). PARTICIPANTS -- Random sample of rural households in each setting (n=275, 707, 910, and 856, respectively). MAIN RESULTS -- In both Mali and Malawi, the wealth proxy correlated highly (r0.74) with the more complex monetary value method. For rural areas of Côte d'Ivoire, it was possible to generate a list of just 10 expenditure items, the values of which when summed correlated highly with expenditures on all items combined (r=0.74, development dataset, r=0.72, validation dataset). Total household expenditure is an accepted alternative to household income in developing country settings. CONCLUSIONS -- It is feasible to approximate both household wealth and expenditures in rural African settings without dramatically lengthening questionnaires that have a primary focus on health outcomes." -- Online Abstract